Human rights literacies and students' paradoxical understandings of tolerance and respect - Roux, C. (South African Journal of Higher Education, 2017)
Ivanhoe (2009:312) states that the “majority of contemporary Western philosophers who accept the fact of ethical pluralism and take this as a cause for concern, tend to argue for tolerance in the face of such differences”. He further argues that tolerance is mostly understood as the “uncritical acceptance of a range of competing and mutually irreconcilable values or forms of life”. During the past two years, students at South African public Higher Education Institutions (HEI) were raising more distinct voices about the underlying social issues and economic disparities experienced at these institutions. Many of the students’ #MustFall protests, starting in 2015, have played out on campuses of South Africa’s universities. Protesters have been critical of HEI’s involvement (especially management) and argue that they did not go far enough to respond to the concerns of students’ grievances and demands. Management did not reflect or indicate the urgency to meet or improve their needs on social issues prevalent to higher education communities. Two incidents portrayed in the visual media during the #FeesMustFall protests, (September and October 2016) at two different universities, portrayed the complexities of being tolerated or respected. These incidents triggered a review of captured data of a funded research project (2012-2015:2018) on human rights literacies. The data captured in this project derived from South African (2013) and both South Africa and international (2015) students’ understanding of human rights literacies. The survey and interviews also focussed, inter alia on students’ understanding of respect and tolerance as a human right. This article reflects on the complexities underlying these two concepts and thereafter responds to the paradoxes identified in local and international students’ understanding of tolerance and respect.